Takhrij and Syarah Hadith of Agrotechnology: The Glory of Farming - Alyaa Surya Rizqia; Cecep Hidayat; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad about the glory of farming. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research is that farming has been compulsory for every Muslim since the time of the Prophet, and has been done until now. The conclusion of this research is the takhrij and syarah hadith of the Prophet Muhammad regarding the glory of farming which will bring glory to the end of the day for everyone who does it.